Characteristics of Sleep Slow Waves in Children and Adolescents - Kurth, Salomé (Associated Professional Sleep Societies, LLC, 2010)
STUDY OBJECTIVES: Slow waves, a major electrophysiological characteristic of non-rapid eye movement sleep, undergo prominent changes across puberty. This study provides a detailed description of sleep slow waves of prepubertal children and mature adolescents to better understand the mechanisms underlying the decrease of activity in the slow-wave frequency range across puberty. DESIGN: All-night sleep electroencephalographic recordings were performed for baseline and after sleep deprivation. SETTING: N/A. PARTICIPANTS: Eight prepubertal children (Tanner 1/2, 11.9 ± 0.8 years, 3 boys) and 6 mature adolescents (Tanner 4/5, 14.3 ± 1.4 years, 3 boys). INTERVENTIONS: Thirty-six hours of sleep deprivation. MEASUREMENTS AND RESULTS: Both during baseline and after sleep deprivation, a steeper slope of slow waves was observed in prepubertal children (351.0 ± 49.5 μV/s), compared with mature adolescents (215.0 ± 27.2 μV/s, P < 0.05; mean of first 5 NREM sleep episodes from baseline), even accounting for overall amplitude differences. CONCLUSIONS: Based on a recent thalamocortical computer model, these findings may indicate a greater synaptic strength of neurons involved in the generation of sleep slow waves in prepubertal children, compared with mature adolescents. Such increased synaptic strength may be due to greater density or greater efficacy of cortical synapses or both. CITATION: Kurth S; Jenni OG; Riedner BA; Tononi G; Carskadon MA; Huber R. Characteristics of sleep slow waves in children and adolescents. SLEEP 2010;33(4):475-480.